2013
DOI: 10.4069/kjwhn.2013.19.4.275
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Self-Identity and Menopausal Symptoms on Level of Depression in Middle Aged Women

Abstract: Purpose:The purpose of this study was to identify the factors influencing self-identity and menopausal symptoms their influence on level of depression in middle-aged woman. Methods: Participants were 135 middle-aged women who were living in city B, were 45-60 years old, informed of study purpose, and agreed to participate. Data were collected from December, 2012 to January, 2013 using scales measuring depression, self-identity, and menopausal symptoms. Data were analyzed using t-test, ANOVA, Scheffé test, Pear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
1
3
0
2
Order By: Relevance
“…Further, severity of psychological and physical symptoms and knowledge level on menopause are shown to be affecting attitude. [11] Therefore, there should be a change of trend where their conditions are accurately measured and provided beforehand, so that they can positively react to the change and nurture the ability to control their behavior. [15] C. mobile intervention for wellness of woman in menopause There already exists mobile applications for menopause management.…”
Section: B Recognition Factors Actions and Attitude Towardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, severity of psychological and physical symptoms and knowledge level on menopause are shown to be affecting attitude. [11] Therefore, there should be a change of trend where their conditions are accurately measured and provided beforehand, so that they can positively react to the change and nurture the ability to control their behavior. [15] C. mobile intervention for wellness of woman in menopause There already exists mobile applications for menopause management.…”
Section: B Recognition Factors Actions and Attitude Towardsmentioning
confidence: 99%
“…It was found that the level of knowledge on menopause is positively correlated to the behavior to improve their health. Most maintained healthy lifestyle if they have adequate information [11]. Symptoms differ from each menopausal stage [8].…”
Section: Introductionmentioning
confidence: 99%
“…Low-level depression, slightly high-degree of self-identity and relatively less climacteric symptoms are found in Korean middle-aged women. 4 Menopause knowledge is low in Korean women. Middle-aged women with more knowledge of menopause were more likely to manage menopause better, and those having more negative attitudes toward menopause were found to experience negative menopause symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…그동안 국내 연구로는 우울의 영향요인 (Chang & Cha, 2003;Jun, Kim, Lee, & Kim, 2004), 운동이 중년여성의 우울에 미 치는 영향 (Koji, Toshihiko, Katsutoshi, Masashi, & Yoshiharu, 2007), 폐경기 여성의 우울 (Deek & McCabe, 2004;Han & Lee, 2013;Kim & Kim, 2013;Kwon, Nah, Kim, Joe, & Cho, 2016), 중년여성의 우울에 사회적 지지가 미치는 영향 (Kim & Kim, 2013;Koji et al, 2007), 만성질환과 우울과의 관계 (Kwon et al, 2016;Seo, Choi, Kim, Lee, & Oh, 2017…”
Section: ) 건강증진을 위해 좀 더 적극적적인 중재가 필요한 집단unclassified